Implementation of Digital Feedback Control with Change Rate Limiter in Regulating Water Flow Rate Using Arduino - Sitompul, Erwin; Putra, Ridha Muhlita; Tarigan, Hendra; Silitonga, Arthur; Bukhori, Iksan (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
Water flow rate control is crucial in applications where it determines operational efficiency in applications such as agriculture, hydroponics, industrial processes, and hydrology. This research presents two algorithms for a simple and reliable digital water flow control: Error-Sign-based Control (ESC) and Error-Value-based Control (EVC). These algorithms are equipped with a change rate limiter to avoid excessive control output increase. They were compared qualitatively with the conventional digital PID controller. Subsequently, they were implemented and tested in a water circulation system. The control loop consisted of a microcontroller, water flow rate sensor, and submersible DC water pump with a supporting motor driver. The controllers were given a control task to follow a 150-second reference trajectory with a changing set point every 30 seconds. The performance measures of Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) were utilized to assess the performance of the control algorithms. EVC with a change rate limiter of 10% delivered the best performance with an MAE of 0.40 and RMSE of 0.97. EVC provides simple and reliable control of the water flow rate system due to its easy tuning, quick tracking response to set point changes, and solid regulating performance. Further work in the implementation of the control scheme in other applications is encouraged.